Integrating SDG‑Themed Digital Authentic Texts in Communicative Language Teaching for Developing Students’ Digital Literacy - Angga Prasongko; Erwin Hari Kurniawan; Ninik Farikha (E-Link Journal, 2026)
As higher education increasingly prioritizes digital competence, pedagogical models must move beyond tool integration toward design-driven digital literacy development. This study examines how embedding Sustainable Development Goal (SDG)-themed digital authentic texts within a Communicative Language Teaching (CLT) framework facilitates digital competence in a technology-enhanced university classroom. Accordingly, this study was conducted to find How does the integration of SDG-themed digital authentic texts within a CLT framework facilitate the development of undergraduate students’ digital literacy. Using a descriptive qualitative design, the study was conducted over a ten-week instructional intervention involving 28 undergraduate English Language Education students. Data were generated from classroom observations, multimodal digital works, reflective journals, and semi-structured interviews. The analysis was informed by digital competence dimensions framed by UNESCO. Findings show that SDGs functioned as epistemic and ethical substance, intensifying students’ critical engagement with multimodal digital texts. Through structured cycles of exposure, analysis, production, and reflection, students demonstrated progressive development in organized information evaluation, multimodal meaning-making, ethical digital participation, and digitally mediated communicative competence. The study developments an SDG-Embedded Techno-Pedagogical Mediation Model, arguing that digital literacy development arises from the meeting of global sustainability discourse, multimodal digital works, and communicative instructional instruments. By highlighting contextual relevance and pedagogical design as primary drivers of digital competence, this study contributes a design-oriented framework to technology-enhanced learning research.